2011
DOI: 10.1063/1.3596947
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the relationship between topology and designability of conformations

Abstract: Protein structures are evolutionarily more conserved than sequences, and sequences with very low sequence identity frequently share the same fold. This leads to the concept of protein designability. Some folds are more designable and lots of sequences can assume that fold. Elucidating the relationship between protein sequence and the three-dimensional (3D) structure that the sequence folds into is an important problem in computational structural biology. Lattice models have been utilized in numerous studies to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…The extent of designability of conformations of proteins is intimately linked to their topology [1]. Topology of folded proteins is deduced from three-dimensional all-atom structures, expressing them as a reduced set of nodes interacting via links.…”
Section: Introductionmentioning
confidence: 99%
“…The extent of designability of conformations of proteins is intimately linked to their topology [1]. Topology of folded proteins is deduced from three-dimensional all-atom structures, expressing them as a reduced set of nodes interacting via links.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the topology of each structure and its interaction network were described using graph features. The graph features used in this analysis were the same features used in our earlier study with the lattice models (Leelananda et al, 2011). Fifteen graph features (or protein conformation interaction graph invariants) were used in this analysis (Fig.…”
Section: Generation Of Contact Graphs and The Use Of Graph Featuresmentioning
confidence: 99%
“…In our earlier study performed on lattice proteins, all possible compact conformations within a set of 2D and 3D lattice spaces were explored, and we found that complementary interaction graph features can be used to predict protein designabilities (Leelananda et al, 2011). It was suggested that the topologies of lattice conformations are important determinants of the extent of their designability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Chapter 2, work on the designability of two-dimensional (2D) and threedimensional (3D) lattice models is discussed. Section 2.1 is based on a published article (Leelananda et al, 2011b). Here, graph features of contact maps are employed to describe the topology of lattice models, and the relationship between these features and the designability of models is explored.…”
Section: A Guide To the Present Studymentioning
confidence: 99%